Religious Music as a Medium of Da'wah Hadith Perspective: Case Study of Alma Voice at Al-Mawaddah Islamic Boarding School - Nur Izzah Islamy; Ibnu Azka; Fathur Baldan Haramain (IJIBS, 2025)
Da'wah is the process of conveying Islamic teachings to the public through various methods adapted to the times. One contemporary medium used in da'wah is religious music. Music functions not only as entertainment but also as a means to deliver moral and Islamic messages. In Islamic boarding schools (pesantren), religious music has become an innovative form of da'wah that effectively attracts public attention, especially among the younger generation. This study aims to explore the role of religious music as a da'wah medium from the perspective of Hadith, using a case study of Alma Voice, a religious music group from Al-Mawaddah Islamic Boarding School for Girls in Ponorogo. This research uses a qualitative method with a descriptive-analytical approach, combining literature review of Hadiths related to music and art with field observations of da'wah practices carried out by Alma Voice. The findings show that Alma Voice uses music to spread Islamic values through lyrics that promote love for the Prophet Muhammad, encourage piety, and strengthen Islamic brotherhood (ukhuwah Islamiyah). From the Hadith perspective, music is permissible as a means of da'wah as long as it does not contain elements contrary to Islamic law. This study concludes that religious music can be an effective communication tool for da'wah within the pesantren context when aligned with Qur'anic and Hadith-based values.